Responsiveness Pusat Pelayanan Kapal Kalimas Terpadu dalam Mewujudkan Pembangunan Konektivitas Maritim Indonesia - ‘Aini, urrotul (Universitas Airlangga, 2021)
AbstractRealizing the Development of Indonesian Maritime Connectivity needs to be supported by excellent public services. Indonesia as a maritime country needs to improve to improve global shipping. This study aims to determine the responsiveness of the integrated Kalimas ship service center in realizing the development of Indonesian maritime connectivity. This study uses a descriptive qualitative approach. The research locus is at Pelindo III Tanjung Perak Surabaya branch. Collecting data by observation, interviews and literature study. Checking the validity of the data used data triangulation. Analysis of the data used qualitative analysis of the interactive model. The results of the research on the responsiveness of the integrated Kalimas ship service center, the service speed indicator is considered fast. For indicators of officer responsiveness to complaints and difficulties experienced by service users related to the services provided have also been assessed as good and responsive. Meanwhile, the responsiveness indicator in providing information to service users is also considered quite good.Abstrak Mewujudkan Pembangunan Konektivitas Maritim Indonesia perlu didukung pelayanan publik prima. Indonesia sebagai negara maritim perlu berbenah untuk meningkatkan pelayaran global. Penelitian ini bertujuan untuk mengetahui responsiveness pusat pelayanan kapal kalimas terpadu dalam mewujudkan pembangunan konektivitas maritim indonesia. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Lokus penelitian di Pelindo III cabang Tanjung Perak Surabaya. Pengumpulan data dengan observasi, wawancara dan studi pustaka. Pemeriksaan keabsahan data digunakan triangulasi data. Analisis data digunakan analisis kualitatif model interatif. Hasil penelitian responsiveness pusat pelayanan kapal kalimas terpadu indikator kecepatan pelayanan dinilai sudah cepat. Untuk indikator ketanggapan petugas terhadap keluhan dan kesulitan yang dialami oleh pengguna layanan terkait pelayanan yang diberikan juga sudah dinilai baik dan tanggap. Sedangkan untuk indikator ketanggapan dalam pemberian informasi kepada pengguna layanan juga dianggap sudah cukup baik